2023
DOI: 10.1017/s1366728923000287
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-language input and infant volubility: Friend or foe?

Abstract: Language mixing is a common feature of many bilingually-raised children's input. Yet how it is related to their language development remains an open question. The current study investigated mixed-language input indexed by observed (30-second segment) counts and proportions in day-long recordings as well as parent-reported scores, in relation to infant vocal activeness (i.e., volubility) when infants were 10 and 18 months old. Results suggested infants who received a higher score or proportion of mixed input in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(251 reference statements)
0
0
0
Order By: Relevance
“…The relation remained significant after removing the effect of the English-only blocks. Moreover, within contexts involving language mixing, infants who heard more words were also the ones who produced more vocalizations [24]. Bail et al reported a positive correlation between total vocabulary and conceptual vocabulary in both of the languages that the toddler in 3 of 15 their study had been exposed to and the degree of language mixing of the parents during a 13 min play session [25].…”
Section: Vocabulary Learning In Children In a Mixed-language Environmentmentioning
confidence: 94%
“…The relation remained significant after removing the effect of the English-only blocks. Moreover, within contexts involving language mixing, infants who heard more words were also the ones who produced more vocalizations [24]. Bail et al reported a positive correlation between total vocabulary and conceptual vocabulary in both of the languages that the toddler in 3 of 15 their study had been exposed to and the degree of language mixing of the parents during a 13 min play session [25].…”
Section: Vocabulary Learning In Children In a Mixed-language Environmentmentioning
confidence: 94%